1983
DOI: 10.1007/bf00251825
|View full text |Cite
|
Sign up to set email alerts
|

Molecular heterogeneity of glucagon in normal subjects and in patients with glucagon-producing tumours

Abstract: Summary.The gel filtration profiles of immunoreactive glucagon as measured by region-specific radioimmunoassays were studied in plasma samples from eight patients with glucagon-producing tumours and in extracts from five of these tumours, and compared with profiles in plasma samples from 24 normal subjects, and pancreas extracts from four patients without pancreatic turnouts. In all extracts a component corresponding in size to the glucagon marker constituted the majority of the immunoreactivity, but small amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 27 publications
(34 reference statements)
5
53
1
Order By: Relevance
“…The major component of the enteroglucagons present in human plasma is a molecule that is homologous to glicentin, whereas oxyntomodulin constitutes a minor fraction. However, specific measurement of oxyntomodulin, which requires chromatography, has been carried out in only a few studies [7,8], and it is possible that oxyntomodulin, which is a prominent component of the enteroglucagons in extracts of the distal intestine in humans [9], may occasionally be present in plasma in concentrations similar to those obtained in this study. In a recent study using high pressure liquid chromatography for the determination of oxyntomodulin in rat plasma, Kervran et al [19] found that oxyntomodulin was the predominating circulating enteroglucagon and that its concentration increased markedly in response to a meal.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The major component of the enteroglucagons present in human plasma is a molecule that is homologous to glicentin, whereas oxyntomodulin constitutes a minor fraction. However, specific measurement of oxyntomodulin, which requires chromatography, has been carried out in only a few studies [7,8], and it is possible that oxyntomodulin, which is a prominent component of the enteroglucagons in extracts of the distal intestine in humans [9], may occasionally be present in plasma in concentrations similar to those obtained in this study. In a recent study using high pressure liquid chromatography for the determination of oxyntomodulin in rat plasma, Kervran et al [19] found that oxyntomodulin was the predominating circulating enteroglucagon and that its concentration increased markedly in response to a meal.…”
Section: Discussionsupporting
confidence: 51%
“…A similar peptide has been identified in human ileal mucosa extracts [4-61 and, by means of gel filtration of concentrated samples collected after carbohydrate meals [7,8], in human plasma. Recent studies from our laboratory have shown that a peptide that corresponds to oxyntomodulin is secreted from the isolated perfused ileum upon stimulation with intraluminal glucose.…”
Section: Introductionmentioning
confidence: 88%
“…This peptide is insulinotropic [34], and probably explains the insulinotropic activity of some preparations of "gut glucagon", described in earlier publications. However, as a circulating hormone in humans, its concentration is probably too low to influence insulin secretion under physiological circumstances [35]. GLP-1 secretion is stimulated by the presence of nutrients in the lumen of the gut (but additional neural or endocrine mechanisms could also operate) [36], and the secretion of GLP-1 throughout the day is highly correlated to the release of insulin [37].…”
Section: Glucagon-like Peptide-1 (Glp-1)mentioning
confidence: 99%
“…Nevertheless, it was not as potent as glucagon. It was therefore questionable whether this molecule, which circulates in low concentrations [9], would contribute to the incretin effect.…”
Section: Discovery Of Glucagon-like Peptide-1mentioning
confidence: 99%